Sustainability of Sharia Effects: Evidence from the Markets of Indonesia and Malaysia - Adi Gunanto; Siti Aisyah; Mohammad Ridwan; Sofyan Syamsuddin; Munzir; Sunarmi (Universitas Muhammadiyah Yogyakarta, 2024)
This study is designed to assess the empirical impact of increased profitability, leverage, and carbon emission disclosure on the scale of sustainability reporting. A quantitative method was chosen as the primary approach, relying on secondary data as a source of information. Observations were conducted on manufacturing entities listed in the Sharia Securities List in Indonesia and Malaysia during the period from 2021 to 2023, using purposive sampling techniques resulting in a sample of 105 companies. Descriptive and verificative statistical methods were employed for data analysis, including panel data regression using fixed effects models. Eviews 12 software was adopted as the analytical tool. The empirical findings of this research indicate that increased profitability and carbon emission disclosure significantly contribute to the expansion of sustainability reporting disclosure. On the other hand, increased leverage does not have a significant negative impact on the scale of sustainability reporting disclosure.